Studying Human Nature and Its Relation to the Islamic Education Process (Universitas Muhammadiyah Sidoarjo, 2015)
Human is a unifiedbody and soulin a reciprocal relationshipwithhis worldand each other. Inunity, there is a physicalelementthat makes themanwith the worldoutside himself. In the philosophy ofIslamic educationhumans are creatures who potentiallyhave opportunitiestolearn.Education is essentially aconscious activityofguidancefor man toportray himselfas aservant ofAllahappropriately andoptimally. Thus,educationis agradual activity, programmedandsustainable. Environmental factorsinfluence onhuman nature, these factors caneven affectthe human personality. Spiritualpotentialowned byhuman beingshascertain tendencies. Therefore, the task ofIslamic educationis to develop, conserve, andenhancethetendency ofbad togoodtrend.